2018
DOI: 10.1017/jpa.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable new genus and species of the planktonic shrimp family Luciferidae (Crustacea, Decapoda) from the Cretaceous (Aptian/Albian) of the Araripe Sedimentary Basin, Brazil

Abstract: A new genus and species of the planktonic shrimp family Luciferidae,Sume marcosin. gen. n. sp., is described and illustrated from material collected in calcareous shale of the late Early Cretaceous (Aptian–Albian) Romualdo Formation, Araripe Basin, northeastern Brazil. The material is very well preserved, including the antennae, stalked eyes, second and third maxillipeds, pleopods, and uropods, and represents the first described fossil of the family Luciferidae.UUID:http://zoobank.org/fdf825b8-6fe9-42ae-8fc7-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Amino acid results place this perplexing decapod with Sergestidae (pelagic shrimp), as suggested by morphological analysis, especially spermatophore morphology [51,52]. Crown dendrobranchiates diverged in the Late Devonian (Figure 3), with the two main clades Sergestoidea and Penaeoidea both diverging in the Pennsylvanian (about 73 Myr prior to the estimates of Ma et al [53], and over 100 Myr older than the minimum ages suggested by Robalino et al [54]). Although our mean posterior age of crown Penaeidae (134 Ma) is younger than the phylogenetically justified Late Jurassic crown fossil Antrimpos speciosus [54], which we did not use as a calibration, our 95% CI encompasses the fossil age of 151 Ma.…”
Section: (C) Evolutionary History Of Shrimpmentioning
confidence: 81%
See 1 more Smart Citation
“…Amino acid results place this perplexing decapod with Sergestidae (pelagic shrimp), as suggested by morphological analysis, especially spermatophore morphology [51,52]. Crown dendrobranchiates diverged in the Late Devonian (Figure 3), with the two main clades Sergestoidea and Penaeoidea both diverging in the Pennsylvanian (about 73 Myr prior to the estimates of Ma et al [53], and over 100 Myr older than the minimum ages suggested by Robalino et al [54]). Although our mean posterior age of crown Penaeidae (134 Ma) is younger than the phylogenetically justified Late Jurassic crown fossil Antrimpos speciosus [54], which we did not use as a calibration, our 95% CI encompasses the fossil age of 151 Ma.…”
Section: (C) Evolutionary History Of Shrimpmentioning
confidence: 81%
“…As it was outside of Sergia + Deosergestes, and we did not sample Acetes, we allow P. deliciosa to calibrate the clade including Lucifer. Note that a likely member of Luciferidae was recently discovered from the same deposits [53], and could be appropriate for this node as well.…”
mentioning
confidence: 99%
“…However, the fossils from the Araripe Basin are very well known for their excellent state of preservation and paleobiological diversity (Martill, 1988). On the other hand, the knowledge about fossil shrimp in the Araripe Basin is basically restricted to taxonomic works (Martins-Neto & Mezzalira, 1991a; Martins-Neto & Mezzalira, 1991b; Maisey & Carvalho, 1995; Santana et al, 2013; Pinheiro, Saraiva & Santana, 2014; Saraiva, Pinheiro & Santana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Romualdo and Crato Formations of the Araripe Basin have the following fossil shrimp species: the Crato Formation shows the Carideans Beurlenia araripensis (Martins-Neto & Mezzalira, 1991a; Martins-Neto & Mezzalira, 1991b); in the Romualdo Formation were described three species of shrimps, the Sergestoid Paleomattea deliciosa (Maisey & Carvalho, 1995), the Penaeoid Araripenaeus timidus (Pinheiro, Saraiva & Santana, 2014) and the planktonic shrimp family Luciferidae, Sume marcosi (Saraiva, Pinheiro & Santana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As primeiras publicações datam dos anos de 1940 e 1950, e entre este último e o ano de 1990 inexistem trabalhos na literatura. O interesse pelos fósseis desses crustáceos tornou-se mais frequente a partir da primeira década do século XXI, com os trabalhos de Alencar et al (2018Alencar et al ( , 2020; Pinheiro et al (2014); Prado, Calado & Barreto (2019); Santana et al (2013); Saraiva et al (2018). O que foi possível devido à realização de coletas sistemáticas nas formações Crato e Romualdo, da Bacia do Araripe, evidenciando a potencialidade paleontológica desses invertebrados nos afloramentos cretácicos da região, em particular àqueles localizados no estado do Ceará.…”
Section: Introductionunclassified